2008
DOI: 10.1080/13625180802273530
|View full text |Cite
|
Sign up to set email alerts
|

The influence of peers on risky sexual behaviour during adolescence

Abstract: The sexual norms of peers influence youths' individual attitudes and behaviours. Gender differences in sexual socialization also play a role. Both aspects must be taken into account when devising prevention programmes concerning adolescent sexuality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 27 publications
5
43
0
7
Order By: Relevance
“…Therefore, this is a key time to target backpackers with sexual health promotion messages via, for example, backpacker guide books, websites and medical services used in preparation for their journey [19]. With perceived norms of peer sexual behaviour impacting on young people's own behaviour [20], such information should stress that most backpackers having sex with new partners abroad routinely use condoms (here 59.0% of 'single' backpackers having sex).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this is a key time to target backpackers with sexual health promotion messages via, for example, backpacker guide books, websites and medical services used in preparation for their journey [19]. With perceived norms of peer sexual behaviour impacting on young people's own behaviour [20], such information should stress that most backpackers having sex with new partners abroad routinely use condoms (here 59.0% of 'single' backpackers having sex).…”
Section: Discussionmentioning
confidence: 99%
“…Peer influence in romantic and sexual behavior Close friends, romantic peers, and broader peer contexts have been found to influence adolescent sexual behavior and adolescents' decisions to engage in romantic and sexual relationships (Ali & Dwyer, 2011;Baumgartner, Valkenburg, & Peter, 2011;Crockett, Raffaelli, & Shen, 2006;Kennett, Humphreys, & Schultz, 2012;Potard, Courtois, & Rusch, 2008). In one study, a majority (42%) of non-sexually active youth reported feeling pressure from romantic partners or platonic peers to become sexually active (Potard et al, 2008).…”
Section: Sex Differences In Adolescent Developmentmentioning
confidence: 99%
“…In one study, a majority (42%) of non-sexually active youth reported feeling pressure from romantic partners or platonic peers to become sexually active (Potard et al, 2008). Generally, having sexually active platonic peers has been found to lead to more positive attitudes towards sexual activity, earlier sexual debut, increased sexual activity, and an increased number of sexual partners (Ali & Dwyer, 2011;Furman et al, 2007;Santor, Messervey, & Kusumakar, 2000).…”
Section: Sex Differences In Adolescent Developmentmentioning
confidence: 99%
“…In addition, a number of studies have found that perceptions of peers' sexual attitudes and behaviors predict sexual risk behavior among teenagers. [13][14][15] Teenagers who sext may hold similar beliefs, perceiving their peers, parents, and even the media to approve of sexual activity. Sexting may also relate to difficulties with managing emotions.…”
mentioning
confidence: 99%